Strategi Pemberdayaan Pemuda Masjid oleh BKPRMI dalam Meningkatkan Partisipasi Sosial di Kota Medan - Nugroho, Bayu; Lubis, Suwardi; Asfriyati, Asfriyati (Jurnal Pemberdayaan Masyarakat, 2025)
The Indonesian Youth Mosque Communication Body (BKPRMI) plays a crucial role in empowering youth in mosques, including in Medan City. This article aims to analyze the strategies implemented by BKPRMI in increasing the social participation of mosque youth in Medan City. This research uses a qualitative approach with in-depth interviews of BKPRMI members and mosque youth. The findings show that BKPRMI implements leadership training, social programs, and knowledge development to increase the involvement of mosque youth in social and religious activities. High social participation among mosque youth contributes to the creation of a more cohesive and caring community. The study also reveals that, despite various challenges, BKPRMI's role remains significant in empowering mosque youth in Medan City.